Pengaruh Komunikasi Internal Terhadap Kinerja Karyawan - Munthe, Kristina; Tiorida, Ermina (Jurnal Riset Bisnis dan Investasi, 2017)
The organization consists of a number of people who works together or interact one another to achieve a goal. Internal communication is communication that occurs in organization or company, either horizontal or vertical. The purpose of this research is to examine the impact of internal communication (vertical and horizontal) to the performance of employees. The questionnaire is distributed to 117 employees of PT Promedrahardjo Farmasi Industri. Data analysis technique that used is validity test, reliability test and simple linear regression with program SPSS 20.0 for Windows. The result concludes that to improve the performance, management needs to provide more formal or non-formal forum for their employees to say their honest opinions and build up the intimacy between employees and management.